Activities of a Lawyer in Receiving a Principal and Preparing for Participation in Court as a Representative - Bebutova Zarnigor Faxriddinovna (European Science Publishing, 2024)
This article examines the relationship between a lawyer and a client in trust and examines the rules of professional ethics that a lawyer must observe in this regard. It also explains what a lawyer should pay attention to during a conversation with a client who trusts him, and what actions he should take to participate in the trial.
Keywords: lawyer, trustee, professional ethics, interview, preparation for the process.